(untitled) (Journal of Educational Sciences, 2018)
The paper highlights the issues of improving the quality of teaching schoolchildren and the factors that influence it, such as the content of education, the use of educational technologies, the technological culture of the teacher, the didactic conditions of the influence of educational technologies on the quality of instruction, the introduction of trilingual education, the possession of information technologies, etc. The paper presents a model for the effective use of personal-oriented educational technologies, which contributes to the improvement of the quality of teaching. The use of technology implies the nomination of the necessary conditions that constitute the essence of the literate implementation of any educational technology. These conditions include such factors as the integrity of the learning process, the systematic use of technology, the performance of each stage of the intended function, the sequence of the technology steps, the correspondence of the results to the intended goals, ensuring the search activity of each student, the quality of the educational and methodological literature, the level of the technological culture of the teacher, theoretically correctly formulated and approved model of training, as well as periodic selection and replacement of variational learning models, etc. Key words: content of education, didactic conditions of educational technologies, model of teaching quality, trilingual education.